The Combination of AFP and “Up-To-Seven” Criteria May Be a Better Strategy for Liver Transplantation in Chinese Cirrhotic HCC Patients - Zhang, Da-li; Feng, Dan-ni; He, Xi; Zhang, Xiao-feng; Li, Li-xin; Li, Zhi-jie; Niu, Xiao-feng; Zhuang, Yun-long; Liu, Zhen-wen; Gao, Xu-dong; Wang, Hong-bo (Frontiers in Oncology, 2022)
Background Orthotopic liver transplantation (OLT) is a life-saving option for patients with hepatocellular carcinoma (HCC), but the expanded OLT criteria remain controversial. Objective The study aimed to explore whether expanded OLT criteria can be applied to Chinese cirrhotic patients with HCC. Methods This retrospective study analyzed risk factors for HCC recurrence and death and compared patients’ tumor characteristics and outcomes in groups of Milan, “Up-to-seven,” and Hangzhou criteria, and groups between met and unmet the combinative criteria of “Up-to-seven” and AFP of < 1000 ng/mL. Results Among 153 patients who underwent OLT for HCC from January 2015 to February 2019 in 4 years of follow-up, 20 (13.1%) patients had HCC recurrence, and 11 (7.2%) had HCC-related death. Multivariate Cox regression analysis showed that preoperative alpha-fetoprotein (AFP) of > 1000 ng/mL (hazard ratio [HR]: 10.05, 95% confidence interval [CI]: 2.45–41.13, P = 0.001) was an independent risk factor for HCC recurrence and HCC-related death (HR: 6.63, 95%CI: 1.31–33.52, P = 0.022). Patients who did not meet Milan criteria but satisfied the “Up-to-seven” criteria had no differences in overall survival (OS) (P = 0.69) and disease-free survival (DFS) (P = 0.35) than patients who met the Milan criteria. The combination of “Up-to-seven” criteria and AFP of < 1000 ng/mL differed significantly (HR: 18.9; 95% CI: 4.0–89.2; P < 0.001). Patients with HCC who met the “Up-to-seven” criteria and AFP of < 1000 ng/mL (n = 121) had excellent survival with 4-year OS of 91.6% (P < 0.001) and DFS of 90.8% (P < 0.001), which is significantly better compared to the other group (n = 32) (OS of 67.5% and DFS of 46.5%) and patients who met the Milan criteria (n = 108, OS of 89.8%, DFS of 89.6%), allowing 28.9% (13/45) of patients who did not meet the Milan criteria to benefit from OLT. Conclusion Chinese cirrhotic patients with HCC who met the combinative criteria of “Up-to-seven” and AFP of < 1000 ng/mL had better survival than those who met the Milan criteria, and these combinative criteria benefited more patients and may become a better option for OLT.